Edukasi Kesehatan Mental Remaja Menggunakan Media Leaflet Pada Anak Sekolah Menengah Pertama - Riskiya Sibarani, Adinda Azima; Lestari, Anisa Ayu; Rizki, Aprida Aulia; Ramadhani, Lutfiah; Vovo, Rahmi; Afrianda, Silvina Mutia; Nisrina, Nisrina (Universitas Muhammadiyah Sukabumi, 2023)
Mental health education for teenagers is very important to increase teenagers' knowledge and awareness about mental health and prevent mental health disorders in teenagers. This research aims to increase students' knowledge about adolescent mental health. This research uses an experimental method with a pretest-posttest design to measure students' level of knowledge before and after conducting youth mental health education using leaflets and short presentations. The research was conducted on 58 junior high school students at SMP Muhammadiyah 61 Tanjung Selamat, Pancur Batu sub-district, Deli Serdang Regency. The results of this activity show a positive trend in increasing students' understanding and knowledge of Mental Health using leaflet media. This is shown by the increase in the percentage of students who have good abilities in the post-test results. As many as 86.6% of class VII students and 100% of class IX students have good abilities. The improvement in the abilities of class VII and class IX students was more significant in the post-test results. The conclusion is that educating using leaflet media can expand the knowledge and understanding of Muhammadiyah 61 Tanjung Selamat Middle School students regarding mental health in adolescents.